(3TQM GdeYdbGJ GdSHYs - (3MSjf Hf CMeO Hf MSjf GdRhRfj, CHh YHO Gddg,J (B486 (3g` s
(3ChdgG (B:s
(3bGd GdbGVi GdCeGe CHh YHO Gddg gPG TQM GdbUGFO GdSHY , CedjJg Ydi MO GdEjLGR hGdGNJUGQ Ydi MSH eG GbJQM Ydi s
(3BNQgG (B:s
(3hgh GdQH hGdTgjO Ydi jhe GdMjGQjf hGdHdGA HdGA Je GdcJGH HMeO Gddg s
(3BNQ UaMGJgG JYbjHIs
(3HChdgG JQLeI ddRhRfi ehLRI efbhdIs
(3fSNI SGOSI JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs